STUNTING PREVENTION STRATEGY BY IMPROVING THE NUTRITIONAL STATUS OF TODDLER : A SYSTEMATIC REVIEW - Fitriana, Ilma; Intan Permatasari, Dela (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: Globally, there has been progress in lowering the rates of linear growth stunting and chronic undernutrition in children under five years old, however many areas still have high rates.Aims : This systematic review is to review stunting prevention strategy with improving status of nutrition in toddler.Methods: This study demonstrated compliance with all requirements by means of a comparison with the standards established by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020. Thus, the specialists were able to guarantee that the research was as current as feasible. Publications released between 2014 and 2024 were considered for this search strategy. This was accomplished by utilizing a number of distinct online reference sites, including Pubmed, ScienceDirect, and SagePub. It was determined that reviews, previously published works, and partially completed works would not be included.Result: In the PubMed database, the results of our search brought up 691 articles, whereas the results of our search on SAGEPUB brought up 2026 articles, our search on SCIENCE DIRECT brought up 4136 articles. The results of the search conducted for the last year of 2014 yielded a total 430 articles for PubMed, 776 articles for SAGEPUB and 2307 articles for SCIENCE DIRECT. In the end, we compiled a total of 8 papers, 6 of which came from PubMed, 1 of which came from SAGEPUB and 1 of which came from SCIENCE DIRECT. We included eight research that met the criteria.Conclusion: In summary, stunting must be managed in order to protect children from its harmful effects. To do this, a variety of linked parties must contribute to the effort. Improving the mother's responsive stimulation and health education might be the first step in improving the nutritional and cognitive state of the kid.